2001
DOI: 10.2166/wst.2001.0078
|View full text |Cite
|
Sign up to set email alerts
|

Study on endocrine disrupting chemicals in wastewater treatment plants

Abstract: From July 1998 to March 1999, a study was made of a total of 27 treatment plants for the principal purpose of understanding the actual condition of endocrine disrupting chemicals (EDCs) in sewage, and the behavior of EDCs in wastewater treatment plants. The results showed actual levels of influent and effluent concentrations of EDCs in sewage. Substances detected above the minimum limit of determination were 15 for wastewater influent and 6 for effluent. Similarly, nonyl phenol ethoxylate and 17 beta-estradiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(63 citation statements)
references
References 0 publications
4
59
0
Order By: Relevance
“…This apparent anomaly in the increase in E1concentration is explained by the biological conversion of E2 to E1 during the treatment process and in the sludge route. This abnormal behaviour has also been observed in previous studies (Nasu et al, 2001;Jurgens et al, 2002;Hashimoto et al, 2007;Ren et al, 2007). This also explains why E1 persist in both the effluent and sludge from the WWTPs.…”
Section: Removal Rates Of Treatment Processessupporting
confidence: 88%
See 1 more Smart Citation
“…This apparent anomaly in the increase in E1concentration is explained by the biological conversion of E2 to E1 during the treatment process and in the sludge route. This abnormal behaviour has also been observed in previous studies (Nasu et al, 2001;Jurgens et al, 2002;Hashimoto et al, 2007;Ren et al, 2007). This also explains why E1 persist in both the effluent and sludge from the WWTPs.…”
Section: Removal Rates Of Treatment Processessupporting
confidence: 88%
“…It exhibited an increase in concentration from influent to effluent in some of the sites. Nasu et al (2001) also showed E2 concentrations increasing from raw influent to primary effluent within Japanese STW (before falling during biological treatment), which suggest that perhaps some further deconjugation was still taking place. In another study of the Japanese STW by Hashimoto et al (2007) a removal efficiency of 11-83 % were reported for E1 in conventional activated sludge plant, with E2 removal of up to 86 %.…”
Section: Introductionmentioning
confidence: 93%
“…Comparable concentration ranges have been reported from Japan (Nasu et al 2000), The Netherlands (Belfroid et al, 1999), Germany (Kuch and Ballschmiter, 2001) and Canada (Ternes et al, 1999b). Somewhat lower levels of E2 (1.1 ng l -1 ) and EE2 (4.5 ng l -1 ) were present in effluent from a Swedish STW, mostly present in unconjugated form, suggesting deconjugation may occur in the sewage system (Larsson et al, 1999).…”
Section: Figure 1 Near Heresupporting
confidence: 58%
“…However, some estrogenic chemicals could not be eliminated by the secondary treatment. It was reported that certain natural and synthetic hormones and alkyl-phenolic surfactants could not be removed during the biological treatment process and their estrogenic effects were even increased or activated (Nasu et al 2001). In comparison, we can conclude that the removal efficiency of estrogenic chemicals from secondary treatment process depends on the chemical characteristics of the sewage.…”
Section: Estrogenic Chemicalsmentioning
confidence: 81%
“…Endocrine disruption activity in WWTP effluents has also been frequently studied (Nasu et al 2001;Murk et al 2002;Alatriste-Mondragon et al 2003). This effect was attributed to a group of chemicals including natural products, pharmaceuticals, and industrial chemicals, which have been shown to be estrogen mimics.…”
mentioning
confidence: 99%